Theoretical and computation modelling of polymer seal life - Ho, Tsz Hang Emily Ting (Cranfield University, 1993)
Elastomer seals are widely used in the petroleum industry. Seal failure can be very expensive, due to losses in production and high maintenance costs. Another aspect of this problem is the difficulty in predicting the working life, of a specific elastomeric seal in a specific application, at the design stage. The objective of the present work is to develop the theoretical and computational seal life model to assist reliable prediction of seal life. Seal life computer software has been developed to model fluid ingress into elastomeric seals and the resulting long term material property changes caused by volume swell and chemical reaction between elastomer and ingressed fluid. The approach used is to model diffusion using a finite element method. This permits application to a wide range of seal geometries. The mathematical model of diffusion is coupled with chemical reaction equations of second order to model chemical ageing processes in the seal. To model the effects of swell, volume of absorbed fluid is coupled with Young's modulus. Physical, as opposed to chemical, stress relaxation is not incorporated since the short time scale of this enable direct measurements to be made. The software has been tested against experimental data for a number of elastomer / operating condition combinations. Satisfactory agreement is obtained for ethylene propylene diene (EPDM) and nitrile rubber aged in air or high pressure water; nitrile and hydrogenated nitrile rubber (HNBR) aged in high temperature, high pressure hydrocarbon liquid. The software has also been found useful for calculating required soak time in planning rig tests for the study of explosive decompression caused by absorbed gas in elastomers. Pending further development of the software, long term prediction of retained sealing force of O-rings in high temperature, high pressure water is calculated from compression set by a semi-empirical approach. Results are compared with experimental data.